Desenvolvimento de equipamento produtor de pasta mineral para aproveitamento dos rejeitos das lamas calcárias e diminuição do impacto ambiental - Ruben Heriberto Olcay Barreda (2012)
In the beneficiation of phosphate has been generating considerable amounts of tails of which the limestone is present, may be reused in accordance with to the characteristics of type of limestone produced. The method more used in the beneficiation of phosphate for disposal of tails is the storage in dams. This approach is not preferred by industriesdue to high volumes of water that are associated without reuse and need of large areas of land. Potentials flailures in dams can cause greats environmental disasters, creation of public indignation, causes of deaths, closure of mining plants and other relevant facts. The tailings disposal in the form of mineral slurry has several advantages compared to conventional tailings dams, for example, needs a much smaller area fordisposal, has a better water recovery, there is less risk of contamination of areas by rupture of dams, reduces contamination of water process enabling the reuse this, facilitates the final recovery of the area among others. The paste mineral technology has developed rapidly trough of the world, especially in Latin America in countries such as Brazil, Chile and Peru. The main objectives of this study was to characterize the solidsample from of sludge tailings of the processing of phosphate of complex mineroquímico Cajati of Vale Fertilizantes Company, through properties physical and chemical such as density (pycnometry simple, gas); granulometry (centrifugal classification and analysis sympatec ), chemical composition (FRX and EDS), mineralogical composition (MEV and DRX); specific surface area (Blaine and BET), evaluation of the influence of flocculant cationic, anionic and not ionic in the limestonesludge, project design, construction and implementation of a laboratory-scale equipment for the production of paste mineral with their main assessments of characteristics of the pastes minerals produced by rheological characterization as viscosity (viscometry), consistency (slump test); fluidity (flume test) and yield stress. The equipment developedfor the production of paste mineral was built in acrylic material of type modular can reach a maximum height of 1.80m also was developed a system of rakes. Were evaluated two types of mixers slurry/flocculant in the feed of equipment of static type and system reactor gerator of flakes called RGF. The main results were: a) intermediate density of the solid material: 2.60(g/cm3) (PS) and 3,06(g/cm3) (PG), b) the size distribuition of the mud is very thin with 100% of the smaller size 30m, c) the FRX and MEV in the sample showed the principal presence of magnesium, calcium, phosphorus, oxygen and small amounts of iron, silicon and sulfur was also detected in the images large amount of fine particles, d) the DRX showed the presence of calcite and dolomite as the principal mineralogical phases in the sample mineral studied, e) thesample showed high value of the ASE by the Blaine method was 0,9758m2/g and BET de 1,972m2/g, f) in tests of discontinuous sedimentation in beakers of 2.000ml under normal conditions showed that the point of compression to a solids concentration in mass of 10% is around 7.200s, g) in the avaliation of flocculant was selected the Bufloc5158 (cationic) by the well performance in tests of sedimentation in dosages of 80g/t and viability of reuse of the clarified water in the process of flotation of apatite; h) in tests of sedimentation semicontinuos with using of recirculating slurry and using flocculants showed a gain about of 6% in the solids concentration in the discharge of equipment, to the series of tests was also demonstrated the best use of the system is withof RGF compared to the static mixer with a gain of 4% in solids concentration in the discharge, i) in concentration profile of the sediment layer there is a phase transition from slurry to paste of low density in the range between 55% and 58% solids by weight; j) the using rakes system was favorable, with a gain of about 7% of solids concentrationin mass, k) the best operating conditions in the equipment after 120 minutes of continuous operation were obtained concentrations in solid mass around 70% in form of paste mineral; l) in the slump tests the mud presented as paste mineral in the range of thickening between 68 and 74% solids by weight; m) in the flume tests were achieved angles of repose above 16 degrees without degree inclination of the gutter with 74% solids in mass, n) in the solids concentration in mass of 70% were obtained values between 1.400cP and 2.700cP, o) in the yield stress the mud phosphate showed a significant increase in the stress of type exponential with values higher than 80Pa from 65% solids by mass confirming the formation of paste mineral since this value.